COMPARATIVE PHARMACOGNOSTICAL STUDY OF THE GENUINE AND MARKET SAMPLES OF THE STEM BARK OF CIRABILWA (HOLPTELEA INTEGRIFOLIA PLANCH.) - T P, *Sinimol; Hameed A, Shahul (International Journal of Ayurveda and Pharma Research, 2018)
Context: The stem bark of Cirabilwa (Holoptelea integrifolia Planch.) is used for treating various disease conditions including Dyspepsia, Flatulence, Colic, Helminthiasis, Vomiting, Skin diseases, Diabetes Mellitus, Haemorrhoids and Rheumatism in traditional system of medicine since ancient times. As a part of a proposed clinical study, sufficient quantity of the plant drug was required to evaluate the antidyslipidemic effects, which was procured from market. Aim: This study was designed to identify and compare the pharmacognostical features of the genuine hand collected samples and market samples of the stem bark of this medicinal plant, so as to prove the genuinity of the market samples before using it for clinical study. Materials and Methods: Macroscopic and microscopic methods were applied to determine the diagnostic features of the shade dried samples of the intact stem bark of both samples of the drug and was compared with the available data. Results: The shape, color, thickness, odour, consistency, fracture and surface characteristics were determined. Compound microscope images showed the presence of ray cells, stone cells, starch grains, rhomboidal crystals in both the samples. Conclusion: The study confirmed the identity of both genuine and market samples. Comparable results were obtained which proved the genuinity of the market samples of the stem bark of Cirabilwa (Holoptelea integrifolia Planch).